2017
DOI: 10.1155/2017/7430193
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Methane‐Rich Saline on Rats with Lipopolysaccharide‐Induced Acute Lung Injury

Abstract: Objective. The aim of this research is to evaluate the protective effects of methane-rich saline (MS) on lipopolysaccharide- (LPS-) induced acute lung injury (ALI) and investigate its potential antioxidative, anti-inflammatory, and antiapoptotic activities. Methods. LPS-induced (20 mg/kg) ALI rats were injected with MS (2 ml/kg and 20 ml/kg) before the initiation of LPS induction. Survival rate was determined until 96 h after LPS was induced. Lung injury was assayed by oxygenation index, lung permeability inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The hallmark of ALI is injury to pulmonary capillary endothelial cells and alveolar epithelial cells and the activation of the innate immune, leading to diffuse edema in pulmonary interstitial and alveolar [ 26 ]. Sun et al showed that methane-rich saline protected the lipopolysaccharide- (LPS-) challenged ALI via antioxidative, anti-inflammatory, and antiapoptotic effects, which had potential to be a new therapy for the treatment of ALI [ 27 ]. According to their results, it showed that the survival period was prolonged significantly after methane-rich saline treatment.…”
Section: The Biological Effects Of Methanementioning
confidence: 99%
“…The hallmark of ALI is injury to pulmonary capillary endothelial cells and alveolar epithelial cells and the activation of the innate immune, leading to diffuse edema in pulmonary interstitial and alveolar [ 26 ]. Sun et al showed that methane-rich saline protected the lipopolysaccharide- (LPS-) challenged ALI via antioxidative, anti-inflammatory, and antiapoptotic effects, which had potential to be a new therapy for the treatment of ALI [ 27 ]. According to their results, it showed that the survival period was prolonged significantly after methane-rich saline treatment.…”
Section: The Biological Effects Of Methanementioning
confidence: 99%
“…An emerging star gas, methane, as the richest organic gas in nature, is colorless, odorless, and nontoxic and possesses reducibility, which has attracted increasing attention in recent years, especially for the treatment of diseases [ 15 ]. Studies indicate that methane plays a unique biological role in anti-inflammatory, antioxidation, antiapoptosis, and other cell protection, which has been confirmed in many different animal experiments [ 16 18 ]. Methane has been shown to exhibit protective effects in hepatic, myocardial, and renal ischemia-reperfusion injury through antioxidative, anti-inflammatory, and antiapoptotic effects [ 19 21 ].…”
Section: Introductionmentioning
confidence: 88%
“…The anti-apoptotic effect is one of the most studied properties of CH 4 . Several studies demonstrated that CH 4 modulates the intrinsic pathway of apoptosis ( 9 11 , 29 , 30 , 55 58 ). The intrinsic pathway of apoptosis, also called the mitochondrial pathway owing to the essential involvement of mitochondria ( 59 ), which are not only the site where anti- and pro-apoptotic proteins interact but also the origins of high range of signal pathways that initiate the activation of caspases through various mechanisms ( 60 ).…”
Section: Ch 4 -Mediated Actions On Apoptosismentioning
confidence: 99%
“…Likewise, in an experimental spinal cord IR scenario, CH 4 was proven to significantly reduce the number of apoptotic cells (confirmed by TUNEL staining) and also the amount of cleaved caspase-3 and caspase-9 proteins and to attenuate cytosolic Cyt c release ( 29 ). In addition, CH 4 -rich fluids significantly reduced the expression of cleaved caspase-3 and also decreased the apoptotic cell number in rodents exposed to LPS-induced acute lung injury ( 58 ). In a hepatic IR model, CH 4 inhalation could effectively attenuate the apoptosis-linked morphological changes in the liver and the TUNEL positivity of hepatocytes ( 11 ).…”
Section: Ch 4 -Mediated Actions On Apoptosismentioning
confidence: 99%